Does Achilles tendon cross sectional area differ after downhill, level and uphill running in trained runners? - Andrews Neves, K.; Johnson, A. W.; Hunter, I.; Myrer, J. W. (Journal of Sports Science & Medicine, 2014)
In this study we examined how hill running affects the Achilles tendon, a common location for injuries in runners. Twenty females ran for 10 min on each of three randomly ordered grades (-6%, 0 and +6%) at speeds selected to match the metabolic rates. Achilles tendon (AT) cross-sectional area (CSA) was imaged using Doppler ultrasound and peak vertical forces were analyzed using an instrumented treadmill. A metabolic cart and gas analyzer ensured a similar metabolic cost across grades. Data were analyzed using a forward selection regression. Results showed similar decreases in AT CSA from pre- to post-run for all three conditions of ~5 to 7% (p = 0.0001). Active peak vertical forces were different across grades (p = 0.0001) with the largest occurring during downhill running and smallest during uphill running. Since changes in AT CSA were not different between grades, each form of running appears equal and acceptable in regards to how the Achilles tendon reacts. That is, the results suggest that the Achilles tendon is affected by downhill, level, and uphill running and a decrease in CSA appears to be a normal response.